Homelands : a geography of culture and place across America - Nostrand, Richard L. (Richard Lee), 1939-; Estaville, Lawrence E. (Lawrence Ernest) (Creating the North American landscape., 2001)
Homelands explores the connection of people and place by showing how aspects of several different North American groups found their niche and created a homeland. It looks at geographical concepts in community settings.